Overcoming challenges: an experience report in amapaense higher education on using educational technologies in the pandemic era (Research, Society and Development, 2021)
In mid-March 2020, the outbreak of the SARS-CoV-2, the virus behind the COVID-19 pandemic, placed the world in an emergency. In view of the high degree of transmission, and according to the WHO recommendations, most governments closed “temporarily” all the educational institutions as a control measure to prevent the dissemination of Covid-19. In this context, the only way found to continue the academic course in the Instituto Macapaense de Melhor Ensino Superior (IMMES) was the sudden change from traditional in-person teaching to remote teaching. For this purpose, Google MEET and Classroom were implemented as the digital online learning platform. Thus, a challenging period began for both academics and teachers. Given this scenario, the present work consists of an experience report on the use of these technologies in higher education in the Amapá state. The main challenges raised in this report were the precariousness of the state's Internet system, a situation that was aggravated by the blackout suffered in the state in November 2020; the lack of professional training in the remote modality (showing the technological gap of a generation of teachers) and the creation of a balance between professional and personal routines. On the other hand, the study also revealed positive aspects of online education, showing that the Google classroom is a useful tool for higher education in view of the factors that still make the return to in-person classes impossible. The coronavirus pandemic forced a sudden adaptation to online learning and the impact of this could permanently change the traditional view on Higher Education.